Pengaruh Pola Asuh Orangtua terhadap Akhlak Siswa : (Kajian terhadap SMPN 2 Satu Atap Desa Bambang) - Roihanah; Nur Diaz, Intan (LP3M Universitas Al-Qolam Malang, 2023)
This study focuses on the influence of parenting on student morals and measures how good the moral level of students is at school. Based on field observations made by researchers while taking Real Work Lectures at the place of research object. This study uses a descriptive quantitative method, which is taking samples from a population to be used as a data collection tool. Control for several non-experimental variables and there is a control group as a comparative group to understand the effects of treatment. In this quantitative method, many tests are carried out, namely validity and reliability tests to determine whether questionnaires can be used as research media or not, classical assumption tests to determine the distribution of data on each dependent and independent variable, multiple linear regression analysis to determine the value of variable coefficients, and hypothesis tests to determine whether there is an influence between dependent variables and independent variables. Based on the results of the study, the average morals of students fall into the category of quite good. Many parents apply democratic parenting to students. Democratic and authoritarian parenting styles have a positive impact on student morals, but not with permissive patterns, namely parenting styles that are more inclined to make children have less good morals. Key words: parenting; education; moral; influence; student